RANCANG BANGUN DAN IMPLEMENTASI SISTEM INFORMASI PIUTANG DAN PENGGAJIAN DENGAN PROGRAM MICROSOFT EXCEL (STUDI KASUS DI PT. SOLO TIRTA MANDIRI) - Pertiwi, Selvi Zailani (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
This study aims to design an accounting information system for accounts receivable and payroll at PT. Solo Tirta Mandiri to create a computerized system that makes it easier for this company to carry out recording activitiesin order to facilitate internal control and increase company revenue by minimizing the risks that occur from manual information systems. This research is a descriptive case study research is the primary data which is taken through documentation, observation, and interview techniques. The data analysis technique uses SDLC (System Development Life Cycle) – Waterfall as an approach to accounting information system design and Microsoft Excel as a system media. The result of this research is a computerized account receivable and payroll accounting information system using the fingerscan machine as an electronic attendance to support data processing. In its implementation, it requires a transition time from a manual system to a new system which needs to be evaluated regularly according to needs and circumstances.